Effect of feeding soybean with different concentrations of zinc compounds on germination of produced seed and initial seedling growth - Nafiseh Sheibany; Sina Fallah; Hossien Barani-Beiranvand; Aliyeh Salehi (علوم و فناوری بذر ایران)
IIn order to evaluate the potential of germination and initial seedling growth of soybean seeds fed with zinc oxide nanoparticles, two experiments (in growth chamber and soil) were performed at Shahrekord University in 2020. The treatments in the maternal plant included different compounds of zinc (zinc oxide nanoparticles with sizes of 38, 59 nm and zinc chloride) and different concentrations (0, 50, 100, 200 and 500 mg/kg soil). With increasing the concentration of zinc oxide nanoparticles, especially 38 nm nanoparticles at a concentration of 200 mg/kg, germination percentage and germination rate (67 and 89%, respectively), radicle length and weight (133 and 356%, respectively), plumule length and weight (135 and 103%, respectively) and as a result, seedling vigor index increased (291%). Significant increase in chlorophyll a, chlorophyll b and carotenoids (28, 333 and 73%, respectively), plant height (41%), leaf area (66%), shoot weight (167%) of seedlings of soybeans fed with 200 mg/kg ZnO 38-nm was observed but at a concentration of 500 mg/kg of zinc compounds the toxic effects on soybean seedlings was observed. In general, it is concluded that feeding soybean plant with zinc oxide nanoparticles can be very effective in increasing the vigor of produced seed.